Transition metal sulfide/hydroxide electrode materials with high specific capacities. Issue 15 (4th July 2022) - Xia, Tong; Umar, Ahmad; Wu, Xiang
Abstract : In this work, we report hybrid NiCo2 S4 @Ni(OH)2 electrode materials on Ni foam by a multi-step hydrothermal approach. The mass capacitance of the prepared sample shows an excellent cycling stability after 10 000 cycles of charge/discharge tests. Abstract : Nowadays, research on energy storage devices is mainly focused on enhancing their electrochemical performance. Among them, electrode materials play an important role. In this work, we synthesised several hybrid NiCo2 S4 @Ni(OH)2 samples by a three-step hydrothermal route. As electrode materials, the obtained flower-like structures can accelerate the transfer of electrolyte ions. They possess a specific capacity of 2899.48 F g −1 at 1 A g −1 and superior cycle stability. Moreover, the assembled hybrid device obtains an energy density of 59.26 W h kg −1 at 1432.07 W kg −1 . Bending tests at different angles indicate that the device possesses excellent mechanical flexibility.